A relação entre os modelos mentais dos empreendedores e o desempenho organizacional de startups do Nordeste brasileiro - Silva, Joenison Batista da (2018)
The way in which the economic scenario is structured can be considered a central factor in the investigation of aspects related to organizational performance. However, internal aspects of the organization can also be influencing factors of performance, for example, the mental models of the entrepreneurs. Mental models represent the perceptual structuring of managers about the decisions to be taken in the organizational sphere and that can end up reflecting on the success or failure of the business. The main objective of this research was to verify the relationship between the mental models and the organizational performance of startups in the Brazilian Northeast, based on the model of De Toni et al., (2014). This research became relevant, considering the high mortality rate of Brazilian startups, reaching about 25% in its first year of operation and 50% before completing 4 years in the market (ARRUDA et al., 2012). The methodology adopted in the research was qualitativequantitative (mixed approach), being divided into two stages. The first stage consisted of semi-structured interviews with 5 (five) entrepreneurs / managers of startups in the Brazilian Northeast, aiming to analyze the perception of these individuals regarding the dimensions investigated. In the second stage, a survey was carried out with 42 managers of startups in the Brazilian Northeast. A Likert-type questionnaire of 5 (five) points was adopted, relating the organizational performance factor to the dimensions of mental models proposed by De Toni et al., (2014), being: Knowledge, Emotional Skills, Linear Mind, Relationships, Mission and Strategy, Creativity and Innovation and Vocation. In the qualitative stage, a strong link was found between the perception of the managers / entrepreneurs interviewed and the dimensions that form the mental models as drivers of performance. Among the 7 dimensions analyzed, it was observed that the dimensions of creativity / innovation and vocation demanded more enthusiasm in the interviewees' statements, demonstrating that the constant search for innovation and satisfaction in managing their own enterprise are essential factors in the search for the best performance. At the end of the qualitative analysis, it was possible to elaborate a model adapted from the original proposed by De Toni et al., (2014), bringing in this model adapted subcategories that make up the respective dimensions, which were captured through the conversations with the interviewees. In a second moment, already in the quantitative stage, descriptive statistical tests were carried out aiming to statistically identify a relation between the mental models and the organizational performance aspect. The results showed that all the dimensions investigated have high agreement rates on the part of the respondents regarding their connection with the performance of the startups. It was verified that the dimensions with the highest relation to the performance factor were Vocation with a general average of 4.70 and the Creativity / Innovation dimension with a general average of 4.47. With this, it is noticed that there was a coherence between the results obtained in the two stages of the research. Among all the dimensions investigated, the Emotional Ability dimension was the one that showed the lowest index of relation with the organizational performance with an average of 3.97. However, even though it is the dimension that obtained the lowest mean of agreement, its index still indicates a good agreement on its link to organizational performance. This research has contributed to the development of studies that interrelate the areas of administration and psychology. In addition, it has provided an expansion in the investigations related to the mental models of managers / entrepreneurs of startups and their relation with the organizational performance factor.